2018
DOI: 10.1111/ajd.12895
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and infection. A clinical practice narrative

Abstract: The Australasian Psoriasis Collaboration has developed a clinical practice narrative with respect to the relationship between psoriasis, its treatment and infection. The cutaneous microbiome of patients with psoriasis is different to those without psoriasis, although the significance of this is unclear. Whilst a wide range of microorganisms has been associated with psoriasis (including β-haemolytic streptococci, Staphylococcus aureus, Porphyromonas gingivalis, Candida albicans, Chlamydia psittaci, human immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 60 publications
2
51
0
1
Order By: Relevance
“…For example, P. gingivalis can colonize the brain and play a central role in the pathogenesis of Alzheimer's disease (34). Infections are also well-known triggers for psoriasis (6, 35). More importantly, there have been studies that have shown an increased concentration of bacterial DNA in the synovial fluid of patients with psoriatic arthritis compared to controls (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, P. gingivalis can colonize the brain and play a central role in the pathogenesis of Alzheimer's disease (34). Infections are also well-known triggers for psoriasis (6, 35). More importantly, there have been studies that have shown an increased concentration of bacterial DNA in the synovial fluid of patients with psoriatic arthritis compared to controls (36).…”
Section: Discussionmentioning
confidence: 99%
“…It is a common disease affecting 0.4–4% of the general population (3, 4). However, the exact cause of psoriasis is unclear, and it is generally believed that genetic factors, environmental risk factors and infections play important roles (5, 6). More importantly, no cure is available for psoriasis at present, and it may last lifelong, which may have a negative impact on the quality of life of the affected people.…”
Section: Introductionmentioning
confidence: 99%
“…severe psoriasis) are inherently at increased risk of developing pneumonias, of any cause. 17 Furthermore, discontinuation of biologic therapy may result in a loss of treatment response when rechallenged and/or development of drug antibodies. If cessation of a biologic is being considered due to the pandemic, patients should be unambiguously counselled on the aforementioned risks.…”
Section: Infection Risk Of Immunomodulator and Biologic Therapiesmentioning
confidence: 99%
“…Of special importance is the possible impact of this pandemic in the management of patients with chronic inflammatory conditions of the skin due to the interruption of activities at many dermatology clinics. This type of patients might also be at higher risk for SARS-CoV-2 infection, as demonstrated before in the case of patients with psoriasis, which is a condition independently associated with an increased risk of serious infections [80]. A special attention should be paid to patients under biological therapies for inflammatory cutaneous disorders [85,116], such as those receiving anti-tumor necrosis factor therapy.…”
Section: Implications Of Covid-19 In Dermatologymentioning
confidence: 87%